The Paradox Of Indonesia's Free And Active Foreign Policy In The Transitional Forum Of The Palestinian Board Of Peace: A Critical Analysis Of Fiqh Siyasah And Islamic Liberation Theology - Rodiatun Mardiah; Fauzan Addinul Jihad; Sultan Maulana Masyriqi (Jurnal Dinamika Global, 2026)
Indonesia's involvement in the Palestinian Board of Peace (BoP), signed in Davos in early 2026, has sparked multidimensional controversy. This study aims to analyze the dynamics, implementation, and anatomy of the paradox within Indonesia's free and active foreign policy regarding the Palestinian BoP through the lens of Islamic law and morality. Utilizing a descriptive-critical qualitative method, this study dissects specific primary data in the form of state documents (the President's Speech at the 2024 D-8 Summit, official claims of the 2026 Davos BoP), civil society archives (the 2026 YLBHI Press Release), and philanthropic institutional reports (BAZNAS and Dompet Dhuafa). The results show that the government exercises dual-track diplomacy through transformative demands at the D-8 Summit and pragmatic participation in the Davos BoP. However, the involvement in Davos triggers a paradox because the reconstruction draft of "The New Gaza" textually reduces the existence of Palestinian sovereignty, as criticized by domestic civil elements. To balance this paradox, non-state actors responded through massive paradiplomacy in the form of Zakat, Infaq, and Sadaqah (ZIS) funding to ensure human security on the ground. Based on *siyasah dauliyah* and liberation theology, a peace agreement (*al-shulh*) is null and void and morally flawed if it legitimizes the security-first and capital-driven architecture of hegemonic powers. In conclusion, the legitimacy of Indonesia's foreign policy faces a crucial moral test; the state must distance itself from pseudo-pacification and absolutely side with the restoration of usurped rights (*istirdād al-ḥuqūq al-maslūbah*) for the full independence of Palestine.